2014
DOI: 10.2478/s11687-014-0230-y
|View full text |Cite
|
Sign up to set email alerts
|

The reduction rate of invasive Ascaris suum eggs number in slurry and humus layers of selected soil types

Abstract: 203 SummaryThe aim of this study was to determine under laboratory conditions the percentage and rate of reduction in invasive Ascaris suum eggs, as well as the maximal time of invasiveness retaining by them in swine slurry and 3 soil types. A. suum eggs were introduced into perforated perlon bags which then were placed in samples of slurry and in humus layers of the soils: podsolic soil, black earth and browned black earth. The experiment was carried out for 44 weeks at 4 and 20 °C. Finally, at 4 °C a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…They are amongst the helminth eggs most resistant to environmental factors. They may survive in the nature for many years; therefore, they tend to accumulate in the environment (soil, water) (Crompton, 2001 ; Papajova and Juris, 2009 ; Olszewska et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are amongst the helminth eggs most resistant to environmental factors. They may survive in the nature for many years; therefore, they tend to accumulate in the environment (soil, water) (Crompton, 2001 ; Papajova and Juris, 2009 ; Olszewska et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Katakam et al [69] demonstrated that in pig slurry stored for 308 days under laboratory conditions at 5 °C 42 % of Ascaris suum eggs were still viable, whereas at 25 °C all eggs lost their viability within this period of time. In turn, Olszewska et al [12] noted that in pig slurry stored for 44 weeks (the same time as in Katakam's research) under laboratory conditions at 4 °C the percentage of invasive eggs of Ascaris suum decreased to a level of 49 %, while in pig slurry stored at 20 °C to 11 %. The study of Kachnic et al [65] also showed that at higher temperatures devitalization of Ascaris suum eggs was increased, however, even after 115 days of raw slurry storage at 42 °C, complete devitalization was not achieved.…”
Section: Microbiological Contamination Of the Environmentmentioning
confidence: 66%
“…Parasite eggs and oocysts can survive in pig slurry from a few days up to several years. The most dangerous are highly resistant to inactivation eggs of Ascaris suum [12,64,69]. According to the literature [4] Ascaris suum eggs at the temperature of 8 °C maintain the vitality in pig slurry for 85 days, and mature proglottids of Taenia solium for 76 days.…”
Section: Microbiological Contamination Of the Environmentmentioning
confidence: 99%
See 2 more Smart Citations